1) Write the two equations in standard form:
-7x - 2y = -13
x - 2y = 11
2) Solve one of the equations for one variable in terms of the other variable:
x = 2y + 11
3) Substitute the expression from step 2 into the other equation:
-7(2y + 11) - 2y = -13
4) Simplify the equation from step 3:
-14y - 77 - 2y = -13
5) Combine like terms:
-16y - 77 = -13
6) Solve for y:
-16y = 64
7) Solve for y:
y = -4
8) Use the value of y from step 7 to solve for x:
x = 2y + 11 = 2(-4) + 11 = 3
9) Determine the solution to the system of equations:
(x, y) = (3, -4)
Put the steps in order that are used to solve the following systems of equations by substitution.
-7x-2y= -13
x-2y = 11
-16y = 64
= x-2y = 11 --> x = 2y + 11
-14y - 77 - 2y = - 13
-7(2y + 11) - 2y = - 13
(3, -4)
-16у - 77 = -13
x + 8 = 11
y = -4
x = 3
x - 2 (-4) = 11
Put the steps above in the right order, only use the numbers I listed above. ONLY USE THE NUMBERS ON THE QUESTION NOTHING ELSE
1 answer